2005
DOI: 10.1111/j.1467-856x.2005.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Policy Communities Back In: The Case of Fire Service Cover

Abstract: It is argued that the concept of a policy community has an enduring value in the analysis of public policy, especially if an emphasis is placed on the way in which ideas are excluded from debates. Historical analysis based on the National Archives using a political science conceptual framework can offer fresh perspectives. The concept is developed through a specification of the conditions that encourage policy community formation and survival. Policy inertia led to a policy that produced a higher rate of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Marsh and Rhodes' typology of policy networks fails to explain the policy outcomes of the 2001 MFD crisis. As recent case studies have demonstrated, the term ‘policy community’ retains its utility as a descriptive tool (for example, Grant 2005). However, very few examples can be found of cases which closely resemble either the policy community or issue network model.…”
Section: Resultsmentioning
confidence: 99%
“…Marsh and Rhodes' typology of policy networks fails to explain the policy outcomes of the 2001 MFD crisis. As recent case studies have demonstrated, the term ‘policy community’ retains its utility as a descriptive tool (for example, Grant 2005). However, very few examples can be found of cases which closely resemble either the policy community or issue network model.…”
Section: Resultsmentioning
confidence: 99%
“…This process occurred in a context where participation in the industry was limited to a relatively small sector of society making regulation a matter of low political salience, where there was limited understanding of the technical aspects of the industry, and where there was initially little appetite on the part of regulators to supply it. As an issue of low political salience with a technical character where there has been reasonably narrow social demand for and institutional supply of regulation, the case meets many of the criteria for regulatory capture outlined in the literature (Grant, 2005; Mattli and Woods, 2009; Pagliari, 2012; Tsingou, 2010). 6…”
Section: From Self-regulation To Formal Regulationmentioning
confidence: 96%
“…These include asymmetries of information between the regulated industry and regulators and society more broadly, a lack of widespread public interest in regulation in a given sphere, the apparently technical nature of the subject of regulation, as well as particular institutional and political contexts (Grant 2005 instance, noted that his firm 'is very much in favour of having its activities incorporated into the regulatory framework where regulation is appropriate and proportionate, because this will be extremely beneficial in building the kind of trust that is necessary for platforms such as ours to succeed'. Rhydian Lewis (Interview 11/7/13) likewise noted that Ratesetter sees an important place for regulation, because it 'will give more confidence, the fact that there's a hygiene factor', and that as a result it favoured regulation because 'ultimately […] people expect it [and] the right regulation does add value and is the right thing to do.…”
Section: From Self-regulation To Formal Regulationmentioning
confidence: 99%
See 2 more Smart Citations